Development of digital mathematics teaching materials to improve student learning outcomes in junior high school - Amir, Nurdiah Anggraeni; Nurhikmah, Nurhikmah; Febriati, Farida (Journal of Research in Instructional, 2025)
This research aims to 1) Identify the needs of math digital teaching materials, 2) Design digital teaching materials for mathematics, 3) Measure the level of validity, 4) Measure the level of practicality, and 5) Measure the level of effectiveness. This research uses an R&D (Research and Development) approach. The development model used, namely ADDIE. This research was conducted at SMP Negeri 4 Sungguminasa class VII. The developed digital teaching materials were validated by material experts and media experts. Trials on 1 teacher, 3 students (individual) and 12 students (small group) to see the practicality of digital teaching materials. Meanwhile, 45 students were involved in the effectiveness test learning. The results of the level of validity of digital teaching materials from the assessment of media expert validators (98.3%) are at a very valid stage and material experts (92.5%) are at a very valid stage. The results at the practicality level obtained (range 91-94%) which was declared very practical. Furthermore, the level of effectiveness of digital math teaching materials was measured by a pretest which obtained 54 in the “low” category and the posttest obtained 91 in the “high” category which showed an increase in student learning outcomes so that it was declared very effective. Based on the results of the analysis, it can be concluded that digital math teaching materials are proven to be valid, practical, and effective in improving student learning outcomes.